Predictors of all-cause mortality for patients undergoing transvenous lead extraction. (3rd October 2022) - Azari, A; Kristjansdottir, I; Gatti, P; Gadler, F
Abstract: Background: Risk assessment of TLE patients may be challenging due to incomplete knowledge about possible risk factors for post-TLE outcomes. The aim of this study was to identify predictors of 30-days and 1-year all-cause mortality including the novel parameter frailty in a large retrospective series of patients undergoing TLE at a high-volume centre. Methods: Medical journals of 893 consecutive patients undergoing TLE between January 1, 2010 and December 31, 2018 were retrogradely analysed. Univariate logistic regression and multivariate analyses were performed to identify risk factors. Results: A total of 893 patients were identified. Local infection was the dominant indication (41.1%) and pacemaker was the most common device (49.4%). Mean age was 65±16 years and 73.0% were males. The median follow up was 3.9 years (IQR, 4.5 years). Within the systemic infection group, Staphylococcus aureus was the main microorganism in the positive blood cultures (44.4%) and 69.4% of the patients had vegetations. The 30-days and 1 year mortality rates were 2.5% and 9.7%, respectively. Per-procedural mortality occurred in 1 patient. Significant risk factors for 30-days all-cause mortality at univariate analysis were anaemia, systemic infection, clinical frailty scales (CFS) 5–7 and stage 5 chronic kidney disease (CKD). Age, CRT-P/D (vs ICD), reduced ejection fraction, anaemia, BMI <25 kg/m 2, CFS 4–7 and CKD stages 3–5 were identified as significant predictors of 1-year all-cause mortality. Within the systemic infection subgroup, leucocytosis and white blood cell count (WBC) 8.8–15x10 9 /L were associated with significant 30-days and 1-year all-cause mortality and CRP 200–300 mg/L and low WBC count correlated with 1-year all-cause mortality. Local infection patients with CRP 100–150 mg/L had an elevated risk for 1-year all-cause mortality. Multivariate analysis identified CKD 5, CFS 5–7 and systemic infection for 30-days all-cause mortality and age, CKD 5, CFS 5–7, systemic infection and BMI <25 kg/m 2 for 1-year all-cause mortality as independent risk factors. Conclusions: Patient-related characteristics, comorbidities and systemic infection independently predicted worse post-TLE prognosis. Several parameters need to be considered when assessing patients for TLE in order to risk stratify the patients and optimize the post-TLE care. Frailty is a novel parameter with significant influence on short and long-term outcome. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Internal funding